Serum testosterone, sex hormone-binding globulin and total calcium levels predict the calcaneal speed of sound in men (Clinics, 2012)
OBJECTIVES: Variations in sex hormones and the calcium balance can influence bone health in men. The present study aimed to examine the relationship between the calcaneal speed of sound and biochemical determinants of bone mass, such as sex hormones, parathyroid hormones and serum calcium. METHODS: Data from 549 subjects from the Malaysian Aging Male Study, which included Malay and Chinese men aged 20 years and older residing in the Klang Valley, were used for analysis. The subjects' calcaneal speed of sound was measured, and their blood was collected for biochemical analysis. Two sets of multiple regression models were generated for the total/bioavailable testosterone and estradiol to avoid multicollinearity. RESULTS: The multiple regression results revealed that bioavailable testosterone and serum total calcium were significant predictors of the calcaneal speed of sound in the adjusted model. After adjustment for ethnicity and body mass index, only bioavailable testosterone remained significant; the total serum calcium was marginally insignificant. In a separate model, the total testosterone and sex hormone-binding globulin were significant predictors, whereas the total serum calcium was marginally insignificant. After adjustment for ethnicity and body mass index (BMI), the significance persisted for total testosterone and SHBG. After further adjustment for age, none of the serum biochemical determinants was a significant predictor of the calcaneal speed of sound. CONCLUSION: There is a significant age-dependent relationship between the calcaneal speed of sound and total testosterone, bioavailable testosterone and sex hormone-binding globulin in Chinese and Malay men in Malaysia. The relationship between total serum calcium and calcaneal speed of sound is ethnicity-dependent.